COMPARATIVE ANALYSIS OF CHANGE IN NEUROPHYSIOLOGICAL AND NEUROCHEMICAL INDICATORS IN TRAINED WORKERS EXPOSED TO MERCURY AND VINYL CHLORIDE - Елена Владимировна Катаманова; Ирина Валерьевна Кудаева; Олег Леонидович Лахман; Виктор Степанович Рукавишников; Елена Николаевна Корчуганова; Ирина Михайловна Ещина (Медицина в Кузбассе, 2020)
Objective. Neurophysiological and neurochemical indicators of trainee workers exposed to mercury and vinyl chloride over time.